2020
DOI: 10.1038/s41598-020-77981-4
|View full text |Cite
|
Sign up to set email alerts
|

Kidney segmentation in neck-to-knee body MRI of 40,000 UK Biobank participants

Abstract: The UK Biobank is collecting extensive data on health-related characteristics of over half a million volunteers. The biological samples of blood and urine can provide valuable insight on kidney function, with important links to cardiovascular and metabolic health. Further information on kidney anatomy could be obtained by medical imaging. In contrast to the brain, heart, liver, and pancreas, no dedicated Magnetic Resonance Imaging (MRI) is planned for the kidneys. An image-based assessment is nonetheless feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…For some, alternative techniques may be superior, such as liver fat measurements from the dedicated UKB liver MRI with more accurate fat fraction values. Here, the projected, two-dimensional input format also limits the accuracy of organ measurements, with the proposed kidney volume measurements almost doubling the error previously achieved by segmentation of axial slices [8]. Finally, MRI-based diagnosis of type 2 diabetic status may not be clinically viable, with a specificity of 0.965 and sensitivity of only 0.250 here.…”
Section: Cross-validation Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For some, alternative techniques may be superior, such as liver fat measurements from the dedicated UKB liver MRI with more accurate fat fraction values. Here, the projected, two-dimensional input format also limits the accuracy of organ measurements, with the proposed kidney volume measurements almost doubling the error previously achieved by segmentation of axial slices [8]. Finally, MRI-based diagnosis of type 2 diabetic status may not be clinically viable, with a specificity of 0.965 and sensitivity of only 0.250 here.…”
Section: Cross-validation Resultsmentioning
confidence: 98%
“…They were grouped into four modules, for each of which one network instance with one or more outputs was trained: Body composition, abdominal organs, anthropometric/experimental estimates, and age. The available reference values for these regression targets originate from previously shared atlas-based segmentation results [2], manual analyses [3], DXA imaging [1], and prior neural network segmentations of the liver and kidneys [8]. Across all subjects, 73% of these values were not available through UKB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on machine learning‐based renal segmentation using neural networks reported processing times as good as 1 to 10 s per subject 76‐78 . Although these processing times are superior to our analytic approach, the effort needed to setup meticulously annotated imaging data that can be used to train, validate and test artificial intelligence algorithms must also be included in order to make a fair benchmarking of processing times.…”
Section: Discussionmentioning
confidence: 96%
“…In the US, the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) has compiled a large database of T1w and T2w MRI images of patients with ADPKD [96], [97] fueled from the CRISP consortium and its related studies [25], [98]. Besides dedicated renal imaging databases, cohort studies like the UK Biobank or the German National Cohort might be valuable resources to further foster renal image segmentation and its evaluation [99]. However, these resources are not Open Access, e.g.…”
Section: Datasets and Databases Relevant To Kidney Image Segmentationmentioning
confidence: 99%